KEANEKARAGAMAN TUMBUHAN PEKARANGAN DI BTN RUMAK GRIYA ASRI, DESA RUMAK, KECAMATAN KEDIRI, KABUPATEN LOMBOK BARAT - Adinda Tribuana Putri; Slamet Mardiyanto Rahayu (Nusadaya Journal of Multidiciplinary Studies, 2025)
Rumak is a village in Kediri District, West Lombok Regency. The study was conducted using observational methods. Based on the study, it was found that yard plants in BTN Rumak Griya Asri, Rumak Village, Kediri District, West Lombok Regency had an H’=2.65, indicating moderate diversity, moderate distribution, and moderate community stability.